Relationship between physical activity, fitness and brain morphology in youth - Pasanen, Riikka (2017)
Growing evidence has displayed a relationship between physical activity, fitness and cognitive functions, yet the underlying mechanisms and changes in brain morphology explaining this connection are still quite unknown. The current study examined whether physical activity or physical fitness is related with regional brain volume of cortical thickness in youth.